PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA KELAS VII SMPN 1 SUMBERGEMPOL TULUNGAGUNG - Silfi, Riza Kurnia; Umatin, Choiru (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2019)
This research aims to determine the effect of guided inquiry learning model on social studies motivation and learning outcomes of class VII students of SMP 01 Sumbergempol Tulungagung. The method in this research uses quantitative methods. The sample in this research amounted to 70 students with 34 students of experimental class and 32 students of control class. Data analysis using T-test and Mannova tests. The results of this research show: 1) the influence of a guided inquiry learning model on student learning motivation. Hypothesis testing obtained t count (13.673) t table (1.995) then accept H_0. 2) The influence of guided inquiry learning model on student learning outcomes. Hypothesis testing obtained t count (15.433) t table (1.995) then accept H_0. 3) There is a significant influence of guided inquiry learning model on student motivation and learning outcomes. Based on the results of the manova test, the significance value is 0,000. This value is below the probability value of 0.05 (0,000 0,05). It is known that this test shows H_a received then H_0 is rejected. This means that there is a significant influence between the use of a guided inquiry learning model on motivation and learning outcomes of class VII students of SMPN 1 Sumbergempol Tulungagung. This research contributes to creating active, creative and effective learning so that students' motivation and learning outcomes can increase.Keywords: inquiry; motivation; learn results